Conjoint fluctuations of PFC-mediated processes and behavior: An investigation of error-related neural mechanisms in relation to sustained attention. (October 2021) - Chidharom, Matthieu; Krieg, Julien; Pham, Bich-Thuy; Bonnefond, Anne
Abstract: The ability to detect errors, which derives from the medial prefrontal cortex (mPFC), is crucial to maintain attention over a long period of time. While impairment of this ability has been reported in patients with sustained attention disruption, the role mPFC-mediated processes play in the intra-individual fluctuation of sustained attention remains an open question. In this context, we computed the variance time course of reaction time (RT) of 42 healthy individuals to distinguish intra-individual periods of low and high performance instability, assumed to represent optimal and suboptimal attentional states, when performing a sustained Go/NoGo task. Analysis of the neurophysiological mechanisms of response monitoring revealed a specific reduction in the error-related negativity (ERN) amplitude and frontal midline theta power during periods of high compared to low RT variability, but only in individuals with a higher standard deviation of reaction time (SD-RT). Concerning post-error adaptation, an increase in the correct-related negativity (CRN) amplitude as well as the frontal lateral theta power on trials following errors was observed in individuals with lower SD-RT but not in those with higher SD-RT. Our results thus show that individuals with poor sustained attention ability exhibit altered post-error adaptation and attentional state-dependent efficiency of error monitoring. Conversely, individuals with good sustained attention performances retained their post-error adaptation and response monitoring regardless of the attentional periods. These findings reveal the critical role of the action-monitoring system in intra-individual behavioral stability and highlight the importance of considering attentional states when studying mPFC-mediated processes, especially in subjects with low sustained attention ability.